Effects of corn gluten feed and dried distillers grains with solubles on Boer-type goat growth performance - Whipple, Brendan D.; Crane, Alison R.; Lattimer, James M.; Jones, Cassandra K. (My University, 2019)
Goats are becoming more and more popular in the United States, increasing 211% in the last 15 years. There is very little data that can be found on economical diets for goats. Most diets for goats are based on soybean meal (SBM). This study aimed to determine a cheaper alternative feed for SBM in Boer-type goats using corn gluten feed (CGF) and dried distillers grains with solubles (DDGS). CGF and DDGS are a significantly cheaper alternative to SBM, as SBM cost $216.69 per ton, CGF costs $177.88 per ton, and DDGS costs $184.98. Seventy-five Boer-type goats, approximately 70 d of age and weighing 26.9+- 0.2 kg were used. In a completely randomized design, goats were randomly assigned to pens of 3, with treatment randomly assigned to pen, pen was the experimental unit. Goats and feeders were weighed weekly. Treatments were isocaloric and isonitrogenous, but varied in protein source: 1) soybean meal; 2) 100% DDGS/0%CGF; 3) 66%DDGS/33%CGF; 4) 33%DDGS/66%CGF; 5) 0%DDGS/100%CGF. Data was analyzed using the GLIMMIX procedure of SAS (v. 9.4, Cary, NC), with 0.05 as the accepted alpha. There were no detected differences in (P>.05) final BW, ADG, ADFI, or G:F by increasing levels of CGF. Any diet that corn co products were used the feed cost was reduced by approximately $.04 kg of feed. This led to the result that corn co-products lower the cost of feed per goat (P=.0008). However, there was no evidence showing a significant difference in feed cost per kg of gain. This study concludes that feeding CGF or DDGS can be an economic replacement diet for SBM.
Keywords: Spring 2019